Horizontal Vibration of Pile in Transversely Isotropic Saturated Soil Based on Saturated Porous Medium Theory - Linchao Liu; Qifang Yan (Journal of Applied Mathematics)
In order to consider the influence of liquid phase and soil anisotropy, the soil around the pile is considered a transversely isotropic saturated porous medium, and a horizontal dynamic model of transversely isotropic saturated soil-pile is established. Based on Beor’s saturated porous medium theory and the constitutive equation of transversely isotropic media, the horizontal dynamic control equation of transversely isotropic saturated soil is obtained without considering the vertical displacement. The horizontal vibration of transversely isotropic soil layers was solved using the potential function and separation of the variable method, and the horizontal and radial displacements of the solid soil skeleton of transversely isotropic saturated soil were obtained. The horizontal force of transversely isotropic saturated soil on a single pile was also obtained. On this basis, the horizontal dynamic equation of a single pile in transversely isotropic saturated soil was established, and the horizontal vibration of the pile foundation was solved using the initial parameter method, and the horizontal dynamic impedance of a single pile in transversely isotropic saturated soil is obtained. The influence of soil anisotropy parameter, liquid-solid coupling coefficient, diameter-length ratio, and modulus ratio on the horizontal dynamic impedance of a single pile in transversely isotropic saturated soil was analyzed through numerical examples. The analysis results show that the anisotropy parameters δ1, diameter-length ratio r0/H, and modulus ratio Ep/C66 have a significant impact on the horizontal dynamic impedance of pile foundation in transversely isotropic saturated soil, and the influence of anisotropy on the horizontal vibration of pile foundation should not be ignored. The influence of the liquid-solid coupling coefficient on the horizontal dynamic impedance factor is related to frequency to a certain extent.